Transdisciplinaridade e plantas medicinais: uma visão integrada para ações em educação e saúde - Chechetto, Fátima [UNESP]; Ming, Lin Chau [UNESP] (My University, 2012)
This essay intend to reflect about the transdisciplinarity as a contribution to integrating health and education actions involving the theme “medicinal plants”, given its multidimensional nature. To this end, seeking to understand the meaning of the transdisciplinary vision, since their roots or origin and its connection with the science of the 21st century, based on complex systems. In the course of the deliberations, discusses the need to adopt some principles for the conduct of disciplinary actions in the area of medicinal plants as: diversity in unity, participatory democracy, social-ecological democracy, the sectoral articulation, the pursuit of sustainable development, the exchange of knowledge between technicians and the exchange of scientific knowledge and popular science integration, art, culture and spirituality, management of conflicts through dialogue and the dialectic between the local and global levels.

O presente ensaio visa re etir sobre a transdisciplinaridade como contribuição a integração de ações em educação e saúde que envolvem a temática “plantas medicinais”, dado seu carácter multidimensional. Para tanto, busca compreender o signi cado da visão transdisciplinar, desde suas raízes ou origem e de sua ligação com a ciência do século XXI, baseada em sistemas complexos. No decorrer das re exões, discute sobre a necessidade de adoção de alguns princípios transdisciplinares para a condução de ações na área de plantas medicinais como: a diversidade na unidade, a democracia participativa, a democracia ecológico-social, a articulação inter-setorial, a busca do desenvolvimento sustentável, a troca de saberes entre técnicos e a troca de saberes cientí cos e populares, a integração de ciência, arte, cultura e espiritualidade, a administração de con itos por meio do diálogo e a dialética entre o local e global.
Transdisciplinarity and medicinal plants: an integrated vision for actions on education and health
Keywords: Medicinal plants; Transdisciplinarity; Education; Health; Plantas medicinais; Transdisciplinaridade; Educação; Saúde